Individual asbestos exposure: smoking and mortality--a cohort study in the asbestos cement industry. Issue 9 (September 1990) - Neuberger, M; Kundi, M
Abstract : A historical prospective cohort study comprised all persons employed from 1950 to 1981 for at least three years in the oldest asbestos cement factory in the world. From 2816 persons eligible for the study, record based estimates and measurements of dust and fibres and histories of smoking based on interviews were used to calculate individual exposures over time. After observation of 51, 218 person-years and registration of 540 deaths, underlying causes of death for this cohort were compared with those for the regional population on the basis of death certificates. Deaths from lung cancer in asbestos cement workers were higher (standard mortality ratio (SMR) 1.7), but after adjustment for age and sex specific smoking habits this was not significant (SMR 1.04). The study had a probability of greater than 92% of detecting a smoking adjusted SMR of 1.5 or more. Using the best available evidence (including necropsy records) 52 deaths were assigned to lung cancer and five to mesothelioma. Life table analyses confirmed the predominant influence of smoking on lung cancer. Mesothelioma was associated with the use of crocidolite in pipe production. From present working conditions with much lower concentrations of chrysotile and no crocidolite no more occupational cancers are expected in the asbestos cement industry.